HUBUNGAN TUNGAU DEBU RUMAH, PAPARAN ASAP ROKOK DAN RIWAYAT PENYAKIT KELUARGA TERHADAP KEJADIAN ASMA BRONKIAL PADA ANAK USIA 5 – 10 TAHUN DI WILAYAH KERJA PUSKESMAS LEMPAKE KOTA SAMARINDA TAHUN 2016 - Sri Evi New Yearsi Pangadongan; Agustina Rahyu; Selvy Pasulu (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
Bronchial Asthma generally starts from childhood which is condition where respiration channel experiences constriction because of hyperactivity with some specific stimulation which cause inflammation. Some risk factors are smoking exposure of cigarette smoke, weather changes, mite on house dirt, pet and history of family sickness. The purpose of this research is to know Relation of mite on house dirt, exposure of cigarette smoke  and history of family sickness with bronchial asthma incident to child 5 – 10  years old on working area of Puskesmas Lempake Samarinda City in 2016. Method which used was analytic survey with Case Control approaching. The total sample was 36 children which consisted of 18 case group and 18 control group with matching by using age and gender which submitted with Purposive Sampling technique. Data Analysis used Chi Square with wrong degree ? = 0,005. The result showed that there was relation of mite of house dirt (p = 0,006), history of family sickness (p = 0,001) and no relation with exposure of cigarette smoke (p = 0,370) with bronchial asthma incident to child 5 – 10 years old on working area of Puskesmas Lempake Samarinda City in 2016.